Wage distributions by bargaining regime: linked employer-employee data evidence from Germany - Karsten Kohn; Alexander C. Lembcke (Institute for the Study of Labor (IZA), 2007)
Using linked employer-employee data from the German Structure of Earnings Survey 2001, this paper provides a comprehensive picture of the wage structure in three wage-setting regimes prevalent in the German system of industrial relations. We analyze wage distributions for various labor market subgroups by means of kernel density estimation, variance decompositions, and individual and firm-level wage regressions. Unions' impact through collective and firm-level bargaining mainly works towards a higher wage level and reduced overall and residual wage dispersion. Yet observed effects are considerably heterogeneous across different labor market groups. There is no clear evidence for wage floors formed by collectively bargained low wage brackets which would operate as minimum wages for different groups of workers.
Keywords: 330; Lohnverhandlungen; Lohnstruktur; Maßzahl; Schätzung; Deutschland